1992
DOI: 10.1111/j.1476-5381.1992.tb09026.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanism of 5‐HT1 receptor‐induced smooth muscle contraction in dog saphenous vein

Abstract: 1 We have investigated the mechanism of smooth muscle contraction evoked by activation of 5-HT1-like receptors in dog isolated saphenous vein. 2 In the presence of the 5-HT2 receptor antagonist, ritanserin (0.1pM), concentration-effect curves (lOnM-300pM) for 5-hydroxytryptamine (5-HT)-induced smooth muscle contraction were biphasic. This could be attributed to a direct action on 5-HT1-like receptors at low concentrations of 5-HT (10nm-1OpM) and an indirect (through the release of noradrenaline from sympatheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
4
21
0
Order By: Relevance
“…The latter was based on the observations that: (1) sumatriptan, a selective 5-HT 1 -like receptor agonist (Hoyer et al 1994), failed to mimic 5-HT-induced hypotension Perren et al 1989;De Vries et al 1997b); and (2) the 5-HT 1 receptor family is, by definition, negatively coupled to adenylyl cyclase (Hoyer et al 1994), a transductional system usually associated with vasoconstriction rather than vasodilatation, as previously demonstrated in the canine saphenous vein (Sumner et al 1992). In this respect, it has recently been shown in rats that the orphan receptor mediating peripheral hypotension is identical to the 5-HT 7 receptor .…”
Section: Carlos M Villalón · David Centurión · Guadalupe Bravo · Petmentioning
confidence: 58%
“…The latter was based on the observations that: (1) sumatriptan, a selective 5-HT 1 -like receptor agonist (Hoyer et al 1994), failed to mimic 5-HT-induced hypotension Perren et al 1989;De Vries et al 1997b); and (2) the 5-HT 1 receptor family is, by definition, negatively coupled to adenylyl cyclase (Hoyer et al 1994), a transductional system usually associated with vasoconstriction rather than vasodilatation, as previously demonstrated in the canine saphenous vein (Sumner et al 1992). In this respect, it has recently been shown in rats that the orphan receptor mediating peripheral hypotension is identical to the 5-HT 7 receptor .…”
Section: Carlos M Villalón · David Centurión · Guadalupe Bravo · Petmentioning
confidence: 58%
“…Nifedipine also reduced the tonic maximum contractions to 5-HT and sumatriptan. Sumner et al (1992) also showed a similar depression of maximum contractions to 5-HT and sumatriptan in the dog isolated saphenous vein, a tissue that is known to contract sensitively and maximally to sumatriptan (Humphrey et al, 1988). Interestingly, the tonic contractions to other constrictor agonists like U46619 and endothelin-1 in the human coronary artery were unaffected by nifedipine (Cocks & Stork, unpublished data).…”
Section: Agonistmentioning
confidence: 72%
“…In the present study, the protein kinase C inhibitor, H-7, attenuated the 5-HT-induced increase in myofilament sensitivity to Ca2 , implying a role for protein kinase C. The GTP-induced component of the Ca2+-GTP induced contraction was also inhibited by H-7. H-7 can inhibit cyclic nucleotide-dependent protein kinases in addition to protein kinase C (Hidaka et al, 1984), although the possible role of these enzymes in responses to 5-HT will require further study (see Sumner et al, 1992). It has also been suggested that H-7 directly inhibits myosin light chain kinase (Suzuki & Itoh, 1993), but the concentration of H-7 used in the present study did not inhibit contraction to Ca2+, so that the 5-HT-induced increase in Ca2+ sensitivity may well involve protein kinase C. Previous studies on the rabbit mesenteric artery have also shown that H-7 and another protein kinase C inhibitor, staurosporine can inhibit noradrenaline, endothelin and GTP-7-S-induced contractions at fixed [Ca2+]j, and that the protein kinase C activator phorbol 12,13-dibutyrate increased the Ca2+-sensitivity of the contractile filaments (Nishimura et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…5-HT-induced contractions of rabbit saphenous (Towart, 1981) and basilar arteries (Towart, 1981;Cain & Nicholson, 1989;Clark & Garland, 1993), pig coronary artery (Cain & Nicholson, 1989) and dog saphenous vein (Sumner et al, 1992) were almost completely abolished by the removal of extracellular Ca2', or by Ca2+-channel antagonists. Although 5-HT stimulated phosphoinositide hydrolysis in the rat tail artery , 5-HT-induced contractions in this vessel were also abolished by the removal of extracellular Ca2".…”
mentioning
confidence: 94%